2011
DOI: 10.1007/s00170-011-3547-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on dissimilar friction stir butt welding of AA7075-O and AA2024-T4 considering the manufacturing limitation

Abstract: In the present article, the effect of friction stir welding (FSW) parameters on the weldability and the characteristics of dissimilar weld of aluminum alloys, called AA2024-T4 and AA7075-O are investigated. A number of FSW experiments are carried out to obtain high-quality welds by adjusting the rotational and welding speeds. The weldability and blending of two materials are evaluated by using the macrostructural analysis to observe whether making a notch in a threaded cylindrical tool will lead to a better bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Unless, the RS induced at the nugget zone increase up to the level, which can change the fracture location, or the stress concentration arising from the possible weld defects and voids, which occurs in the nugget zone, changes the stress field within the weld zone and makes joints to fracture from the nugget zone. However, the worth noting is that from hardness point of view, the HAZ exhibits the minimum hardness amount the other zones in tempered precipitating aluminum alloys including AA7075-T6 [31,32]. Meanwhile, the previous observations mainly revealed that the minimum hardness in defect-free welds is followed by the fracture [31,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless, the RS induced at the nugget zone increase up to the level, which can change the fracture location, or the stress concentration arising from the possible weld defects and voids, which occurs in the nugget zone, changes the stress field within the weld zone and makes joints to fracture from the nugget zone. However, the worth noting is that from hardness point of view, the HAZ exhibits the minimum hardness amount the other zones in tempered precipitating aluminum alloys including AA7075-T6 [31,32]. Meanwhile, the previous observations mainly revealed that the minimum hardness in defect-free welds is followed by the fracture [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…However, the worth noting is that from hardness point of view, the HAZ exhibits the minimum hardness amount the other zones in tempered precipitating aluminum alloys including AA7075-T6 [31,32]. Meanwhile, the previous observations mainly revealed that the minimum hardness in defect-free welds is followed by the fracture [31,32]. However, when a defect in other zones such as the nugget zone is resulted from an inappropriate welding process, the RS field may have considerable effect on the crack growth and consequently the weld strength.…”
Section: Resultsmentioning
confidence: 99%
“…SPD technology which imposes severe shear deformation can refine the material microstructure and improve comprehensive performance. Aluminum alloy with high strength and good mechanical properties is popular in material preparation [1][2][3]. Aluminum alloy SPD representative technology, equal channel angular pressing (ECAP) [4,5], high-pressure torsion (HPT) [6], reciprocating extrusion, multi-direction forging, and twist extrusion are gradually becoming a hot topic of research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…AA7075 alloy (Al-Zn-Mg-Cu alloy), which is one of the strongest aluminum alloys, is precipitation hardened wrought material commonly used in aircraft parts, gears and shafts, missile parts, aerospace and defence applications [2]. It has gathered wide acceptance in many structural applications due to its high strength to weight ratio, good resistance to corrosion and natural ageing characteristics [3,4].…”
Section: Extended Abstractmentioning
confidence: 99%
“…No additive materials, cover gas or flux is used in the process and this makes FSW technology a strong candidate for joining of the aforementioned materials. In addition, several types of joints such as butt and T butt joints or fillet joints can be simply welded by this significant technology [1].AA7075 alloy (Al-Zn-Mg-Cu alloy), which is one of the strongest aluminum alloys, is precipitation hardened wrought material commonly used in aircraft parts, gears and shafts, missile parts, aerospace and defence applications [2]. It has gathered wide acceptance in many structural applications due to its high strength to weight ratio, good resistance to corrosion and natural ageing characteristics [3,4].…”
mentioning
confidence: 99%